An Analysis Of Project-Based Learning With The Hilokal Application On Enhancing 8th Grade Student Speaking Skills At Smpn 2 Tulangan In Academic Year 2023/2024 - Kristanti, Yesi; Dewi, Ni Putu Artila; Suryantini, Made Detri (STAI Nurul Falah Airmolek, 2024)
Challenge of understanding the effectiveness of PjBL with the Hilokal Application in enhancing speaking skills. The implementation of the Hilokal Application supports and facilitates project-based learning to improve speaking proficiency among 8th-grade students at SMPN 2 Tulangan.The student''s perceptions of the implementation of the Hilokal Application in supporting and facilitating project-based learning to improve speaking proficiency. the research employs a descriptive qualitative approach to analyze the implementation of PjBL with the Hilokal App and its effectiveness in enhancing speaking skills among 8th-grade students at SMPN 2 Tulangan The descriptive qualitative method allows for a comprehensive understanding of the phenomena through detailed observation, interviews, and document analysis providing rich, narrative data that describe the implementation and its outcomesThe findings from this study suggest that the use of PjBL with the Hilokal app is an effective strategy for enhancing English speaking skills among students. The improvements observed in class VIII-D demonstrate the potential of this approach to address common challenges in language learning, lack of confidence, and limited vocabulary.This study aims to explore the implementation of Project-Based Learning (PjBL) with the Hilokal application in enhancing the speaking skills of 8th-grade students. A qualitative descriptive method is used in this study, with data obtained through observation and analysis of conversation video projects created by the students.